Managing essential inputs: the case of methanol supply in biodiesel industry - Goulart, Daniel Franco (Revista de Negócios, 2016)
This paper aims to discuss the ways that biodiesel producers manage the supply chain of methanol, an indispensable input obtained almost exclusively through importation. To build this discussion, it was firstly drawn the main features of the Brazilian biodiesel industry and, after that, it was described the main methanol’s origins, applications and market. It was identified two ways on which biodiesel companies acquire methanol: a) via long-term contracts or b) in the spot market. If the first option means supply safety, the second one means more competitive prices. This qualitative study was built from two different data collection steps: a) participant observation and b) semi-structured interviews.